ANALYSIS OF ACCOUNTING APPLICATION IN AMANAH RIAU KEPRI COOPERATION - Raja Ade Fitrasari Mochtar; Ahmad Tarmizi (VALUTA, 2020)
The research was conducted at the Amanah Riau Kepri Cooperative with the aim to find out whether the accounting applied to the Amanah Riau Kepri Cooperative was in accordance with generally accepted accounting principles. Research data used are primary data and secondary data. Data collection techniques used were documentation and interviews. The results obtained at the Riau Kepri Amanah Cooperative are 1) the journal in the diary still combines all transactions 2) the residual reports of the results of operations at the Riau Kepri Amanah Cooperative still use the profit / loss report format. 3) Amanah Riau Kepri Cooperative has not separated the burden of cooperatives.